Safety aspect of β2-agonists in chronic obstructive pulmonary diesease - Whale, Christopher Ian (2009)
Chronic Obstructive Pulmonary Disease (COPD) presents an enormous public health challenge. Cigarette smoking remains the most important aetiological factor and although legislation to reduce smoking has been introduced in parts of the more developed world, consumption is increasing in many of the poorest parts of the world. With the predicted rise in disease prevalence, COPD is expected to become the worlds third largest cause of death by 2020.